Parenting styles and personal belief in a just world among Chinese children and adolescents: gender, living location, and age as moderators - Wang, Jing; Ye, Yonghong; Wang, Yun; Zeng, Xihua (Frontiers in Psychology, 2024)
Introduction The positive development of the personal belief in a just world (PBJW) plays a vital role in academic achievement and mental health among children and adolescents. Therefore, it is necessary to understand the influencing factors of PBJW better. The association between parenting styles and PBJW has been well established, but whether this association varies among different groups remains an open issue. The present study aimed to examine the strength of the associations between parenting styles and PBJW among Chinese children and adolescents and the role of certain moderators (gender, living location, and age) in these associations. Methods This study employed hierarchical regression and simple slopes analyses to examine data from the National Children's Study of China. The database includes 24,013 Chinese children and adolescents in grades 49 (M = 12.76 years, SD = 1.73), with 53.50% boys. Results The results indicated that (1) authoritative parenting was positively correlated with PBJW; (2) both authoritarian and permissive parenting styles were negatively correlated with PBJW; (3) the positive relationship between authoritative parenting and PBJW was more prominent in urban regions; the negative relationship between authoritarian and PBJW was stronger in urban regions; and the negative relationship between permissive parenting and PBJW was more pronounced among girls and older children and adolescents. Discussion These findings highlight important associations between parenting styles and the development of PBJW among Chinese children and adolescents, and suggest strategies for policy-makers, educators, and parents to improve PBJW for different types of Chinese children and adolescents.